Method for reducing hydrogen embrittlement sensitivity of high-temperature alloy by using pulse current
The pulse current treatment reduces the hydrogen embrittlement sensitivity of high-temperature alloys, solves the problem of time-consuming, energy-consuming and unstable effects of traditional solid solution treatment methods, and achieves a more effective improvement in the anti-hydrogen embrittlement performance of high-temperature alloy materials.
Patent Information
- Application Number
- CN202411716792.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional solid solution treatment methods are difficult to effectively reduce the hydrogen embrittlement sensitivity of high-temperature alloys, and are time-consuming and energy-consuming, making it difficult to meet the continuous improvement of the performance requirements of high-temperature alloys.
The pulse current treatment method is adopted to observe the microstructure of the high-temperature alloy sample, and the morphology and distribution of the delta phase are counted and analyzed. The pulse voltage, pulse current and pulse frequency are set according to the different delta phase morphology and distribution, and pulse current is processed to reduce the hydrogen embrittlement sensitivity of the material.
This method can quickly dissolve the delta phase that is not conducive to the resistance to hydrogen embrittlement, significantly reduce the hydrogen embrittlement sensitivity of high-temperature alloys, improve the anti-hydrogen embrittlement performance of the material, and extend the service life of the high-temperature alloy in a hydrogen environment.
Smart Images

Figure CN119553068A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature alloy anti-hydrogen embrittlement, and in particular relates to a method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by utilizing pulse current. Background Art
[0002] It is widely used due to its excellent high temperature strength, good oxidation resistance and corrosion resistance. However, the service environment of high temperature alloys is usually extremely harsh, often accompanied by high temperature, high pressure and corrosive media. These conditions easily lead to various forms of corrosion and damage to metal materials, among which hydrogen-induced damage is particularly prominent. Hydrogen-induced damage, commonly known as hydrogen embrittlement, is caused by hydrogen atoms penetrating into the metal and gathering at microscopic defects such as grain boundaries, dislocations and inclusions, resulting in a decrease in the plasticity of the material and an increase in brittleness, thereby initiating the initiation and expansion of cracks, and in severe cases, it can lead to the sudden fracture of components. The δ phase in high temperature alloys is a precipitation phase that is not conducive to the resistance to hydrogen embrittlement. Its existence will become the source of inducing hydrogen-induced damage to high temperature alloys. In order to reduce the harm caused by hydrogen embrittlement, the industry often uses solid solution treatment to remove the harmful δ phase to reduce the hydrogen embrittlement sensitivity of the material. However, the traditional solid solution treatment method is time-consuming and energy-consuming to eliminate the δ phase, and the effect of reducing the hydrogen embrittlement sensitivity of high temperature alloys is also unstable. With the continuous improvement of the performance requirements of high temperature alloys, the traditional solid solution treatment method is difficult to meet new application requirements due to its limitations. Therefore, there is an urgent need to provide a new processing method. Summary of the invention
[0003] In order to overcome the problems existing in the prior art, the present invention provides a method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using pulse current.
[0004] A method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using pulse current comprises the following steps:
[0005] S1: sampling the original high-temperature alloy material, obtaining the sample for microstructure observation, and statistically analyzing the morphology and distribution of the δ phase in the sample;
[0006] S2: performing pulse current treatment on the sample according to the morphology and distribution of the δ phase and the set parameters;
[0007] S3: After the treatment is completed, the treated sample is further treated to calculate the hydrogen embrittlement index to evaluate the hydrogen embrittlement sensitivity of the treated sample.
[0008] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the parameters include pulse voltage, pulse current and pulse frequency.
[0009] According to the above aspects and any possible implementation, an implementation is further provided, wherein the pulse voltage is 1 to 24 V, the pulse current is 20 to 500 A, the pulse frequency is 100 to 10000 Hz, and the processing time is 5 min to 60 min.
[0010] According to the aspects described above and any possible implementation method, an implementation method is further provided, wherein the morphology of the δ phase in S2 includes morphology and average size, and the morphology includes needle-shaped or short rod-shaped; the distribution of the δ phase is the area fraction occupied by the δ phase.
[0011] According to the above aspects and any possible implementation, an implementation is further provided, wherein S2 specifically includes: when the δ phase morphology is needle-shaped, the pulse voltage is 10 to 24 V, the pulse current is 300 to 500 A, and the pulse frequency is 5000 to 10000 Hz;
[0012] When the δ phase morphology is short rod-shaped, the pulse voltage is 1-20V, the pulse current is 100-300A, and the pulse frequency is 1000-5000Hz.
[0013] According to the above aspects and any possible implementation, an implementation is further provided, wherein S2 specifically includes: when the average size of the δ phase is less than 5 μm, the pulse voltage is 1 to 15 V, the pulse current is 50 to 350 A, and the pulse frequency is 500 to 6000 Hz;
[0014] When the average size of the δ phase is ≥5 μm, the pulse voltage is 10-24 V, the pulse current is 150-500 A, and the pulse frequency is 2500-10000 Hz.
[0015] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein S2 specifically includes:
[0016] When the δ phase area fraction is less than 50%, the pulse voltage is 1 to 15 V, the pulse current is 20 to 400 A, and the pulse frequency is 100 to 7000 Hz;
[0017] When the delta phase area fraction is ≥50%, the pulse voltage is 15-24V, the pulse current is 100-500A, and the pulse frequency is 1000-10000Hz.
[0018] According to the above aspects and any possible implementations, there is further provided an implementation, wherein the further processing includes electrochemical hydrogen charging and slow strain rate tensile testing.
[0019] According to the above aspects and any possible implementation, an implementation is further provided, wherein the electrochemical hydrogen charging specifically comprises: pre-charging the sample after pulse current treatment in an electrolytic cell filled with a hydrogen charging solution, using a platinum sheet as a counter electrode, and a cathode current density of 10 mA / cm 2 , time is 50h.
[0020] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein the slow strain rate stretching is performed in air at room temperature.
[0021] According to the aspects and any possible implementation methods described above, an implementation method is further provided, wherein the hydrogen embrittlement index is calculated to evaluate the hydrogen embrittlement sensitivity of the treated sample, specifically, the hydrogen embrittlement index of the sample after pulse current treatment is less than the hydrogen embrittlement index of the sample before treatment, which means that the pulse current treatment reduces the hydrogen embrittlement sensitivity of the high-temperature alloy.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The method of the present invention comprises: sampling the original high-temperature alloy material, obtaining the sample for microstructure observation, and statistically analyzing the morphology and distribution of the δ phase in the sample; performing pulse current treatment on the sample according to the morphology and distribution of the δ phase and the set parameters; after the treatment, further treating the treated sample, and calculating the hydrogen embrittlement index to evaluate the hydrogen embrittlement sensitivity of the treated sample. The method of the present invention can quickly dissolve the δ phase that is not conducive to the hydrogen embrittlement resistance of the high-temperature alloy, reduce the hydrogen embrittlement sensitivity of the material, and improve the hydrogen embrittlement resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The morphology and distribution of the δ phase in the sample after treatment in this comparative example 1;
[0025] Figure 2 The morphology and distribution of the δ phase in the sample after treatment in Example 1;
[0026] Figure 3 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0027] In order to better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the specific implementation methods described below, and similar technologies and methods should be considered to be within the scope of protection of the present invention. In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments.
[0028] It should be clear that the embodiments described in the present invention are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0030] like Figure 3 As shown, the present invention provides a method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using a pulse current, comprising the following steps:
[0031] S1: Take samples from the original high-temperature alloy material for microstructural observation, and count and analyze the morphology and distribution of the δ phase;
[0032] S2: according to the morphology and distribution of the δ phase in the material, the initial pulse voltage, pulse current and pulse frequency are set to perform pulse current treatment;
[0033] S3: After the pulse current treatment is stopped, the treated samples are subjected to electrochemical hydrogen charging and slow strain rate tensile tests, and the hydrogen embrittlement index is calculated to evaluate the hydrogen embrittlement sensitivity of the treated materials.
[0034] The method of the present invention utilizes pulse current to replace the traditional solution treatment. The method promotes the dissolution of the delta phase which is not conducive to the hydrogen embrittlement resistance by applying the thermal and non-thermal effects generated by the pulse current, thereby more effectively reducing the hydrogen embrittlement sensitivity of the high-temperature alloy and improving the hydrogen embrittlement resistance of the material.
[0035] Preferably, in step S1, microstructure observation is achieved by using a scanning electron microscope to count the morphology, average size and area fraction of the δ phase. The needle-shaped δ phase with large size and large area fraction will significantly reduce the hydrogen embrittlement sensitivity of the material. At the same time, the difference in the morphology, average size and area fraction of the δ phase will affect the selection of pulse current treatment parameters.
[0036] Preferably, in step S2, the morphology of the δ phase includes shape and average size, and the shape includes needle-shaped and short rod-shaped; the distribution of the δ phase refers to the area fraction of the matrix occupied by the δ phase.
[0037] Preferably, in step S2, the pulse voltage is 1-24V, the pulse current is 20-500A, the pulse frequency is 100-10000Hz, and the treatment time is 5min-60min. Applying pulse current treatment to the sample within this parameter range will quickly dissolve the δ phase and reduce the hydrogen embrittlement sensitivity of the material.
[0038] Further preferably, in step S2, the initial pulse voltage, pulse current and pulse frequency are set according to the morphology and distribution of the δ phase in the material, specifically:
[0039] When the δ phase in the material is needle-shaped, the pulse voltage is 10-24V, the pulse current is 300-500A, and the pulse frequency is 5000-10000Hz. Compared with the pulse current treatment, the hydrogen embrittlement sensitivity of the material is reduced by 30%-50%;
[0040] When the δ phase in the material is in the shape of short rods, the pulse voltage is 1-20V, the pulse current is 100-300A, and the pulse frequency is 1000-5000Hz. Compared with the pulse current treatment, the hydrogen embrittlement sensitivity of the material is reduced by 15%-25%;
[0041] When the average size of the δ phase in the material is less than 5μm, the pulse voltage is 1-15V, the pulse current is 50-350A, and the pulse frequency is 500-6000Hz. Compared with the pulse current treatment, the hydrogen embrittlement sensitivity of the material is reduced by 10%-40%;
[0042] When the average size of the δ phase in the material is ≥5μm, the pulse voltage is 10-24V, the pulse current is 150-500A, and the pulse frequency is 2500-10000Hz. Compared with the pulse current treatment, the hydrogen embrittlement sensitivity of the material is reduced by 17%-45%;
[0043] When the area fraction of the δ phase in the material is less than 50%, the pulse voltage is 1-15V, the pulse current is 20-400A, and the pulse frequency is 100-7000Hz. Compared with the pulse current treatment, the hydrogen embrittlement sensitivity of the material is reduced by 12%-35%;
[0044] When the area fraction of the δ phase in the material is ≥50%, the pulse voltage is 15-24V, the pulse current is 100-500A, and the pulse frequency is 1000-10000Hz. Compared with the pulse current treatment, the hydrogen embrittlement sensitivity of the material is reduced by 20%-60%.
[0045] Preferably, in step S3, after the pulse current treatment is stopped, the treated sample is subjected to electrochemical hydrogen charging and slow strain rate tensile test, and the hydrogen embrittlement index is calculated to evaluate the hydrogen embrittlement sensitivity of the treated material, specifically:
[0046] The electrochemical hydrogenation method is to pre-charge the sample after pulse current treatment in an electrolytic cell filled with a hydrogenation solution (0.5MH2SO4 containing 1g / L thiourea), using a platinum sheet as the counter electrode and a cathode current density of 10mA / cm 2After electrochemical hydrogen charging, different amounts of hydrogen will be charged into the sample, causing different degrees of hydrogen-induced damage to the material, so as to facilitate subsequent comparison of the hydrogen embrittlement sensitivity of the material before and after treatment and under different treatment conditions.
[0047] The slow strain rate stretching is carried out at room temperature. The sample after pulse current treatment is electrochemically hydrogenated and then the elongation of the sample is obtained by slow strain rate stretching, so as to facilitate the subsequent calculation of the hydrogen embrittlement index of the material before and after pulse current treatment.
[0048] The hydrogen embrittlement index for evaluating the hydrogen embrittlement sensitivity of a sample refers to the plasticity loss rate of the sample before and after hydrogen charging: hydrogen embrittlement index = (material elongation before hydrogen charging - material elongation after hydrogen charging) / material elongation before hydrogen charging. The smaller the hydrogen embrittlement index, the lower the hydrogen embrittlement sensitivity of the material and the better the hydrogen embrittlement resistance. If the hydrogen embrittlement index of the sample after pulse current treatment is less than that of the sample before treatment, it means that the hydrogen embrittlement sensitivity of the high-temperature alloy has been reduced after pulse current treatment.
[0049] The method of the present invention is further described below in conjunction with specific embodiments and comparative examples.
[0050] Example 1
[0051] A method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using pulse current, wherein the high-temperature alloy used is a GH4169 alloy in a certain forged state, and the hydrogen embrittlement index of the sample is 38%, comprising the following steps:
[0052] S1: Samples were taken from the original high-temperature alloy material for microstructural observation, where the δ phase morphology was needle-shaped, with an average size of 3 μm and an area fraction of 30%;
[0053] S2: According to the morphology and distribution of the δ phase in the material, the initial pulse voltage was set to 12V, the pulse current was 300A, the pulse frequency was 5000Hz, and the pulse current treatment was carried out for 30min. The surface temperature of the sample was 800℃.
[0054] S3: After the pulse current treatment was stopped, the treated samples were subjected to electrochemical hydrogen charging and slow strain rate tensile tests, and the calculated hydrogen embrittlement index was 26%, which was 32% lower than before treatment.
[0055] Example 2
[0056] A method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using pulse current, wherein the high-temperature alloy used is a GH4169 alloy in a certain forged state, and the hydrogen embrittlement index of the sample is 47%, comprising the following steps:
[0057] S1: Samples were taken from the original high-temperature alloy material for microstructural observation, where the δ phase morphology was needle-shaped, with an average size of 6 μm and an area fraction of 56%;
[0058] S2: According to the morphology and distribution of the δ phase in the material, the initial pulse voltage was set to 20 V, the pulse current was 400 A, and the pulse frequency was 7000 Hz. The pulse current treatment was performed for 30 min, and the sample surface temperature was 900 °C.
[0059] S3: After the pulse current treatment was stopped, the treated samples were subjected to electrochemical hydrogen charging and slow strain rate tensile tests, and the calculated hydrogen embrittlement index was 28%, which was 40% lower than before treatment.
[0060] Example 3
[0061] A method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using pulse current, wherein the high-temperature alloy used is a GH4169 alloy in a forged state, and the hydrogen embrittlement index of the sample is 32%, comprising the following steps:
[0062] S1: Samples were taken from the original high-temperature alloy material for microstructural observation, where the δ phase morphology was short rod-shaped, with an average size of 2 μm and an area fraction of 20%;
[0063] S2: According to the morphology and distribution of the δ phase in the material, the initial pulse voltage was set to 8V, the pulse current was 120A, and the pulse frequency was 1500Hz. The pulse current treatment was carried out for 30min, and the surface temperature of the sample was 750℃.
[0064] S3: After the pulse current treatment was stopped, the treated samples were subjected to electrochemical hydrogen charging and slow strain rate tensile tests, and the calculated hydrogen embrittlement index was 25.6%, which was 20% lower than before treatment.
[0065] Example 4
[0066] A method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using pulse current, wherein the high-temperature alloy used is a GH4169 alloy in a certain forged state, and the hydrogen embrittlement index of the sample is 37%, comprising the following steps:
[0067] S1: Samples were taken from the original high-temperature alloy material for microstructural observation, where the δ phase morphology was short rod-shaped, with an average size of 5 μm and an area fraction of 62%;
[0068] S2: According to the morphology and distribution of the δ phase in the material, the initial pulse voltage was set to 20 V, the pulse current was 300 A, the pulse frequency was 5000 Hz, and the pulse current treatment was performed for 30 min. The surface temperature of the sample was 850 °C.
[0069] S3: After the pulse current treatment was stopped, the treated samples were subjected to electrochemical hydrogen charging and slow strain rate tensile tests, and the calculated hydrogen embrittlement index was 28.1%, which was 24% lower than that before treatment.
[0070] Comparative Example 1
[0071] The high temperature alloy is the same as the forged GH4169 alloy in Example 1, and the hydrogen embrittlement index of the sample is 38%, comprising the following steps:
[0072] S1: Samples were taken from the original high-temperature alloy material for microstructural observation, where the δ phase morphology was needle-shaped, with an average size of 3 μm and an area fraction of 30%;
[0073] S2: no pulse current treatment, treated at 800 °C for 30 min;
[0074] S3: The treated samples were subjected to electrochemical hydrogen charging and slow strain rate tensile tests, and the calculated hydrogen embrittlement index was 30%, which was 21% lower than that before treatment.
[0075] This comparative example does not use pulse current treatment. The hydrogen embrittlement index of the sample treated by solution treatment at the same temperature is higher than that of the sample treated by pulse current. The effect of reducing hydrogen embrittlement sensitivity in this comparative example is not as good as that of the pulse current treatment in Example 1. Figure 1 The morphology and distribution of the δ phase in the sample after treatment in this comparative example are as follows: Figure 2 The morphology and distribution of the δ phase in the sample after treatment in Example 1 show that the pulse current treatment applied in Example 1 accelerates the dissolution of the δ phase, thereby promoting the reduction of the hydrogen embrittlement sensitivity of the material.
[0076] Comparative Example 2
[0077] The high temperature alloy is the same as the forged GH4169 alloy in Example 4, and the hydrogen embrittlement index of the sample is 37%, comprising the following steps:
[0078] S1: Samples were taken from the original high-temperature alloy material for microstructural observation, where the δ phase morphology was short rod-shaped, with an average size of 5 μm and an area fraction of 62%;
[0079] S2: According to the morphology and distribution of the δ phase in the material, the initial pulse voltage, pulse current and pulse frequency are randomly set so that the surface temperature of the sample is 850°C, and the pulse current treatment is carried out for 30 minutes;
[0080] S3: After the pulse current treatment was stopped, the treated samples were subjected to electrochemical hydrogen charging and slow strain rate tensile tests, and the calculated hydrogen embrittlement index was 30%, which was 18.9% lower than that before treatment.
[0081] This comparative example adopts pulse current treatment, but the initial pulse voltage, pulse current and pulse frequency are not set according to the morphology and distribution of the δ phase in the material. Although the surface temperature of the sample remains consistent, the hydrogen embrittlement index of the sample treated with randomly set parameters is higher than that of the sample treated with parameters set according to the morphology and distribution of the δ phase in the material. The effect of reducing hydrogen embrittlement sensitivity in this comparative example is not as good as that in Example 4 where the pulse current treatment is set according to the morphology and distribution of the δ phase in the material.
[0082] It can be seen from the above embodiments and comparative examples that the present invention provides a method for reducing the hydrogen embrittlement sensitivity of high-temperature alloys by using pulse current, by setting initial pulse parameters according to the morphology and distribution of the δ phase in the material, and selecting the optimal parameters therefrom to achieve rapid dissolution of the δ phase, thereby significantly reducing the hydrogen embrittlement sensitivity of the high-temperature alloy, enhancing the material's hydrogen embrittlement resistance, and extending the service life of the high-temperature alloy in a hydrogen environment. The promotion and use of this method has important industrial application value.
[0083] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not depart from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for reducing the hydrogen embrittlement sensitivity of a high-temperature alloy by using pulse current, characterized in that: The steps include: S1: sampling the original high-temperature alloy material, obtaining the sample for microstructure observation, and statistically analyzing the morphology and distribution of the δ phase in the sample; S2: performing pulse current treatment on the sample according to the morphology and distribution of the δ phase and the set parameters; S3: After the treatment is completed, the treated sample is further treated to calculate the hydrogen embrittlement index to evaluate the hydrogen embrittlement sensitivity of the treated sample.
2. The method according to claim 1, characterized in that The parameters include pulse voltage, pulse current and pulse frequency.
3. The method according to claim 2, characterized in that The pulse voltage is 1-24V, the pulse current is 20-500A, the pulse frequency is 100-10000Hz, and the processing time is 5min-60min.
4. The method according to claim 2, characterized in that: The morphology of the δ phase in the S2 includes shape and average size, and the shape includes needle-like or short rod-like. The distribution of the δ phase is the area fraction occupied by the δ phase.
5. The method according to claim 4, characterized in that The S2 specifically includes: when the δ phase morphology is needle-shaped, the pulse voltage is 10-24V, the pulse current is 300-500A, and the pulse frequency is 5000-10000Hz; When the δ phase morphology is short rod-shaped, the pulse voltage is 1-20V, the pulse current is 100-300A, and the pulse frequency is 1000-5000Hz.
6. The method according to claim 4, characterized in that The S2 specifically includes: when the average size of the δ phase is less than 5 μm, the pulse voltage is 1 to 15 V, the pulse current is 50 to 350 A, and the pulse frequency is 500 to 6000 Hz; When the average size of the δ phase is ≥5 μm, the pulse voltage is 10-24 V, the pulse current is 150-500 A, and the pulse frequency is 2500-10000 Hz.
7. The method according to claim 4, characterized in that The S2 specifically includes: When the δ phase area fraction is less than 50%, the pulse voltage is 1 to 15 V, the pulse current is 20 to 400 A, and the pulse frequency is 100 to 7000 Hz; When the delta phase area fraction is ≥50%, the pulse voltage is 15-24V, the pulse current is 100-500A, and the pulse frequency is 1000-10000Hz.
8. The method according to claim 1, characterized in that The further processing included electrochemical hydrogen charging and slow strain rate tensile testing.
9. The method according to claim 8, characterized in that The electrochemical hydrogenation specifically includes: pre-charging the sample after pulse current treatment in an electrolytic cell filled with hydrogenation solution, using a platinum sheet as a counter electrode, and a cathode current density of 10 mA / cm 2 , time is 50h.
10. The method according to claim 8, characterized in that The hydrogen embrittlement index is calculated to evaluate the hydrogen embrittlement sensitivity of the treated sample. Specifically, the hydrogen embrittlement index of the sample after the pulse current treatment is less than the hydrogen embrittlement index of the sample before the treatment, which means that the hydrogen embrittlement sensitivity of the high-temperature alloy is reduced after the pulse current treatment.
Citation Information
Cited By
Method for improving hydrogen embrittlement resistance of steel by using pulse current
CN121023152A